2013
DOI: 10.1073/pnas.1221077110
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Nurr1 maintains fiber integrity and nuclear-encoded mitochondrial gene expression in dopamine neurons

Abstract: Developmental transcription factors important in early neuron specification and differentiation often remain expressed in the adult brain. However, how these transcription factors function to mantain appropriate neuronal identities in adult neurons and how transcription factor dysregulation may contribute to disease remain largely unknown. The transcription factor Nurr1 has been associated with Parkinson's disease and is essential for the development of ventral midbrain dopamine (DA) neurons. We used condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
186
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(195 citation statements)
references
References 33 publications
7
186
2
Order By: Relevance
“…Because other genetic mouse models with a moderate reduction in DA content similar to that of adult Foxa1/2 cKO mice do not lead to an aphagic phenotype (22,77), we therefore speculate that our model represents a scenario whereby a 50% reduction in DA content in combination with a reduction of burst firing together impair both the quantity and the temporal control of DA release in the striatum. This dysregulation primarily contributes to aphagia due to lack of motivation to feed/drink (37), whereas overall activity/motor function remains unaffected.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Because other genetic mouse models with a moderate reduction in DA content similar to that of adult Foxa1/2 cKO mice do not lead to an aphagic phenotype (22,77), we therefore speculate that our model represents a scenario whereby a 50% reduction in DA content in combination with a reduction of burst firing together impair both the quantity and the temporal control of DA release in the striatum. This dysregulation primarily contributes to aphagia due to lack of motivation to feed/drink (37), whereas overall activity/motor function remains unaffected.…”
Section: Discussionmentioning
confidence: 89%
“…4A). In addition, we quantified the expression levels of Pitx3 and Nr4a2, two transcription factors also expressed in adult mDA neurons (22,35). We found that neither Pitx3 nor Nr4a2 expression A B C Fig.…”
Section: Da Transmission Shows Deficits Restricted To Dorsal Striatum Ofmentioning
confidence: 91%
See 1 more Smart Citation
“…This research was elegantly summarized by Dr. Robert Burke in his talk and recent review [9]. The models that were discussed include: AAV/2 human a-syn-A53T in rat [10], AAV/6 human a-syn-WT in rat [11], hBAC-LRRK2 in mouse [12,13], mBAC-Nurr1(fl/fl)XmBACDAT-CreT2 in mouse [14] and Engrailed1 +/-mouse [15,16], and it is likely that there are other models where such changes are yet to be reported. All of them present some form of axonal abnormalities in TH-positive nigrostriatal fibers before the degenerative processes are detected in the cell bodies.…”
Section: Main Textmentioning
confidence: 99%
“…Similar axonal spheroids were described in the post-mortem brains of PD [18] and Diffuse Lewy Body Disease patients [19], and they are also seen in other neurodegenerative diseases such as multiple sclerosis (MS). In aforementioned rodent models, the axo-degenerative processes are accompanied by other axonal abnormalities that mimic findings made in PD, such as loss of dopaminergic phenotype [11,14,15], changes in levels of axonal transport proteins [10], and autophagy markers [15]. 'It is important to emphasize that although this evidence suggests that axons are the first site of degenerative change, this does not necessarily mean that the primary disturbance at the molecular level first occurs in the axons.…”
Section: Main Textmentioning
confidence: 99%